Josef Koudelka and his recordings of Romani songs from 1960s - Andršová, Kateřina (Romano džaniben, 2022)
Josef Koudelka (born in 1938) is one of the world’s most renowned present-day photographers. His photographs of the Roma have been repeatedly exhibited and published. When traveling among the Roma, Koudelka carried with him not only his camera but also a reel-to-reel tape recorder, which he used to record Romani songs, tales, and commentaries. Koudelka’s field collection has not yet been processed, evaluated nor presented to the professional public. This article tries to provide a closer look at and a characterization of a part of Koudelka’s field recordings of Romani folklore, especially in the settlements of Rakúsy and Jarabina (both in Slovakia). They give us a unique opportunity to take a look at the already extinct or already substantially transformed musical world of the Slovak Romani settlements. Koudelka’s recordings significantly enrich the existing knowledge of the repertoire, interpretation solutions of the songs, and the musicality standard of the local Roma at that time. Along with the recordings taken by Eva Davidová and Milena Hübschmannová they represent the earliest field recordings of Slovak Romani folklore.